INCOME INEQUALITY AND WEALTH DISTRIBUTION - Muadifah, Muadifah; Faiq, Faiq; Rizki, Rizki; Muhaimain, Muhaimain (LPPM Universitas Bina Bangsa, 2024)
This article examines income inequality and wealth distribution in Indonesia, analyzing its concept, contributing factors, impact on sustainable development, and mitigation efforts. Employing a descriptive qualitative method, the article analyzes secondary data from various sources, including reports from the World Bank, BPS (Statistics Indonesia), and academic research. The conclusion highlights that income inequality and wealth distribution in Indonesia constitute a serious concern that requires comprehensive addressing through appropriate fiscal, monetary, and social policies. The article delves into the concept of income inequality and wealth distribution, exploring how disparities in income and asset ownership contribute to a skewed distribution of wealth. It further examines the underlying causes of this inequality, including unequal access to education and training, concentrated economic power, uneven infrastructure development, and a flawed tax system. The article then investigates the detrimental impacts of this inequality on economic growth, quality of life, and social stability. Finally, it proposes a range of mitigation strategies, emphasizing the need for integrated solutions involving government, private sector, and community participation.